2016
DOI: 10.21037/jtd.2016.09.61
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of patients <45 years old with esophageal adenocarcinoma comparing to other age groups

Abstract: Background: To analyze the clinicopathological features and prognosis of younger patients with esophageal adenocarcinoma (EAC). Methods: A total of 2,601 patients diagnosed with EAC between 1988 and 2011 were selected from the Surveillance, Epidemiology, and End Results (SEER) database. All patients underwent primary tumor resection and regional lymphadenectomy without preoperative radiotherapy. The patients were into four age groups (<45, 45-59, 60-74, ≥75), with 94, 813, 1,272 and 422 patients in each group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The prognosis of young EAC patients is still controversial. Some studies have reported that young patients with EAC presented with a more advanced stage of the disease and had poorer survival than older EAC patients[11,12,21]. In our cohort, the outcomes of endoscopic treatment for T1 EAC or HGD between both groups were similar.…”
Section: Discussionsupporting
confidence: 52%
“…The prognosis of young EAC patients is still controversial. Some studies have reported that young patients with EAC presented with a more advanced stage of the disease and had poorer survival than older EAC patients[11,12,21]. In our cohort, the outcomes of endoscopic treatment for T1 EAC or HGD between both groups were similar.…”
Section: Discussionsupporting
confidence: 52%
“…A total of 3647 records were identified through database searching and cross-referencing. Overall, 8 studies were included for qualitative synthesis of which 7 studies were included for quantitative analysis (meta-analysis) with 4991 and 4847 patients respectively[ 13 , 20 - 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, owing to being often diagnosed at an advanced stage at the time of consultation, esophageal cancer has a poor prognosis [8]. It is still controversial whether younger patients with EC have a better or worse prognosis than older patients, which draws our attention to which clinicopathological factors affect the prognosis of young patients with esophageal cancer [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%